India : Defining and Explaining Inclusive Growth and Poverty Reduction - Anand, Rahul (IMF Working Papers; Working Paper ;, 2014)
We document the evolution of poverty and inequality across Indian states during the recent period of rapid growth (2004-09), and examine the role of growth and distribution in reducing poverty. Robust economic growth has been a major driver of poverty reduction and inclusiveness in India. We explore the role of economic policies and macrofinancial conditions in explaining inclusive growth and its components, using a new measure of inclusive growth. Social expenditures, spending on education, and educational attainment rates are important for fostering inclusive growth. Macro-financial stability, with particular attention to inflation risks, is also criticial for promoting inclusive growth.